THE INFLUENCE OF BRAND IMAGE, PRICE AND PROMOTION ON CUSTOMER PURCHASE INTEREST IN GOOD DAY CAPPUCCINO SACHET COFFEE AT THE CANTEEN OF MM SMAN 1 SUKATANI KAB. BEKASI - Mega Sri Ningsih; Etty Zuliawati Zed (SEAN Institute, 2023)
This study is motivated by the lack of problems regarding brand image and promotion on buying interest in Good Day Cappuccino sachet coffee products at the MM SMAN 1 Sukatani Canteen which does not match the price offered, so that consumers do not feel they have an interest in buying these products. This study was conducted to determine the effect of brand image, price, and promotion on customer buying interest in Good Day Cappuccino sachet coffee at the MM SMAN 1 Sukatani canteen, Bekasi Regency. The type of research used in this study uses quantitative research methods. The research design is used as a research reference. Structured questionnaires were used to obtain data from respondents. The number of samples was determined based on incidental sampling (by chance), a total of 90 respondents were used for the study. The data was analyzed using multiple regression analysis using the SPSS 29 application. Based on the test results, it shows that the t-count test results (partial) brand image variables partially have a significant effect on buying interest, price and promotion variables partially have no significant effect on buying interest. Based on the results of the F test, it can be concluded that there is a significant influence between brand image (X1), price (X2) and promotion (X3) together on buying interest (Y).